Cross-cultural exploration of stylized performance: traditional Chinese training methods in drama education - ZHANG, Jingying; Musa, Syahrul Fithri (Institute of Advanced Engineering and Science, 2025)
This study explores the effectiveness of stylized performance training in cross-cultural drama education, focusing on how symbolic body language conveys emotions and character intent. Originating from traditional Chinese theatre, stylized training was adapted to help students from diverse cultural backgrounds achieve emotional resonance and cohesive character portrayal. Employing a participatory action research (PAR) design, the 16-week experiment involved performing arts students from six cultures, using iterative feedback and reflective practices to track changes in emotional expression and adaptation to symbolic movements. The training included three phases: basic training, emotional integration, and applied practice. Data was collected through classroom observations, interviews, feedback forms, and peer evaluations. Findings show that participants improved in non-verbal emotional expression, effectively conveying emotions across cultural barriers. Supported by Pavis’s “intercultural theatre” theory and Mead’s symbolic interactionism, the study highlights stylized performance’s potential to enhance cross-cultural emotional resonance in drama education.